Dairy Husbandry and Dairy Products Extension Service publications and records (USAIN State and Local Literature Preservation Project. Iowa.)
This collection contains pamphlets, publications, printed materials, membership materials, correspondence courses, letters and posters. The publication topics include the feeding of dairy cattle, how to improve your dairy herd, and the production of milk and other dairy products. The remainder of the collection consists of the Dairy Herd Improvement Association accounts, applications for membership, receipts, a tester's manual, demonstration information, and posters.